Synthesis and Characterization of a Gold Vinylidene Complex Lacking π‐Conjugated Heteroatoms1. (23rd April 2015) - Harris, Robert J.; Widenhoefer, Ross A.
Abstract: Hydride abstraction from the gold (disilyl)ethylacetylide complex [(P )Auη 1 ‐CCSi(Me)2 CH2 CH2 SiMe2 H] (P =P( t Bu)2 o ‐biphenyl) with triphenylcarbenium tetrakis(pentafluorophenyl)borate at −20 °C formed the cationic gold (β, β‐disilyl)vinylidene complex [(P )AuCCSi(Me)2 CH2 CH2 Si (Me)2 ] + B(C6 F5 )4 − with ≥90 % selectivity. 29 Si NMR analysis of this complex pointed to delocalization of positive charge onto both the β‐silyl groups and the (P )Au fragment. The C1 and C2 carbon atoms of the vinylidene complex underwent facile interconversion (Δ G ≠ =9.7 kcal mol −1 ), presumably via the gold π‐disilacyclohexyne intermediate [(P )Auη 2 ‐CCSi(Me)2 CH2 CH2 Si (Me)2 ] + B(C6 F5 )4 − .